The receptor for advanced glycation end products (RAGE) contributes to the progression of emphysema in mice. - Nisha Sambamurthy; Adriana S Leme; Tim D Oury; Steven D Shapiro (PLoS ONE, 2015)
Several recent clinical studies have implied a role for the receptor for advanced glycation end products (RAGE) and its variants in chronic obstructive pulmonary disease (COPD). In this study we have defined a role for RAGE in the pathogenesis of emphysema in mice. RAGE deficient mice (RAGE-/-) exposed to chronic cigarette smoke were significantly protected from smoke induced emphysema as determined by airspace enlargement and had no significant reduction in lung tissue elastance when compared to their air exposed controls contrary to their wild type littermates. The progression of emphysema has been largely attributed to an increased inflammatory cell-mediated elastolysis. Acute cigarette smoke exposure in RAGE-/- mice revealed an impaired early recruitment of neutrophils, approximately a 6-fold decrease compared to wild type mice. Hence, impaired neutrophil recruitment with continued cigarette smoke exposure reduces elastolysis and consequent emphysema.